Human Factors in Commercial Human Space Operations. (September 2013) - Cuevas, Haydee M.; Zgorski, Rebecca A.; Kring, Jason P.; Caldwell, Barrett S.; Null, Cynthia H.; Henwood, Brienna L.; Fiore, Stephen M.
What was unthinkable as little as five years ago now seems to be on the brink of becoming a reality in the foreseeable future – a world in which commercial space travel is as commonplace as commercial aviation travel is today. The scientific research community will play a vital role in achieving this reality while supporting the safety of both passengers and crews. This will require the application of sound human factors theories, principles, and practices to develop effective training programs and countermeasures as well as to design viable habitats on board commercial space vehicles for these new space travelers. Accordingly, the objective of this multidisciplinary discussion panel will be to identify and discuss the human factors issues that warrant investigation to support the safe and efficient advance of commercial human space operations.